Dìvčinka abo hlopčik? bokal abo čarka? - na materìalì Ukraïns'koho perekladu noveli Gezi Čata Jožìka - Ladányi Erzsébet (2018)
The article presents examples of Ukrainian translation Solutions, based on the short story of the Hungarian novelist Géza Chath. The translations are made for a competition announced by the Hungarian Balassi Institute.